Bagaimana Nilai Perusahaan dan Harga Saham Dipengaruhi Preferensi Risiko Perusahaan : A Literature Review - Indrayani, Lioni; Tukiran, Martinus; Utami, Vicky Nur (UPT Penerbitan Universitas Jember, 2025)
This study aims to explore the impact of corporate risk preferences on company value and stock prices by reviewing existing literature. Company value and stock prices are important indicators of a company's financial health, influenced by various internal and external factors, including the company's approach to risk. Corporate risk preferences refer to the company's strategies and decisions in dealing with uncertainty and potential losses, which are reflected in its investment choices, capital structure, and financing policies. The literature suggests that companies with higher risk preferences tend to make more aggressive investments, which can boost growth but also increase stock price volatility. In contrast, companies with lower risk preferences prioritize stability and conservatism, leading to more consistent valuations. Understanding the relationship between corporate risk preferences, company value, and stock prices is crucial for providing valuable insights to investors, managers, and other stakeholders in making informed financial decisions.